2015
DOI: 10.1007/s11051-015-3048-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of reduction enhancer on a radiolytic synthesis of carbon-supported Pt–Cu nanoparticles and their structural and electrochemical properties

Abstract: In order to clarify the effect of reduction enhancer on the nanoparticle formation process and their structural and catalytic properties, carbon-supported Pt-Cu nanoparticles were synthesized by electron beam irradiation on an aqueous precursor solution in the presence/absence of reduction enhancer. In the absence of reduction enhancer, tetravalent platinum oxide particles of approximately 1 nm in diameter were formed on carbon support with copper barely precipitated, while in the presence of 2-propanol or eth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 46 publications
1
4
0
Order By: Relevance
“…This indicates that the organic stabilizer makes the lifetime of nuclei long enough for all of the copper to be reduced and retained as metallic copper incorporated in Pt lattice and in part reoxidized to copper oxides in the vicinity of platinum. The presence of copper oxide phases was confirmed by the previous X-ray absorption study where the Cu K-edge XANES of Pt-Cu/C was not of metallic Cu alone and the fitting of Cu K-edge EXAFS to a scattering model showed the presence of Cu-O bonds (Kugai et al 2015). Without stabilizer, the lifetime of nuclei is too short for copper to meet platinum leaving some ionic copper unreduced in the suspension together with large platinum-rich particles.…”
Section: Resultssupporting
confidence: 57%
See 1 more Smart Citation
“…This indicates that the organic stabilizer makes the lifetime of nuclei long enough for all of the copper to be reduced and retained as metallic copper incorporated in Pt lattice and in part reoxidized to copper oxides in the vicinity of platinum. The presence of copper oxide phases was confirmed by the previous X-ray absorption study where the Cu K-edge XANES of Pt-Cu/C was not of metallic Cu alone and the fitting of Cu K-edge EXAFS to a scattering model showed the presence of Cu-O bonds (Kugai et al 2015). Without stabilizer, the lifetime of nuclei is too short for copper to meet platinum leaving some ionic copper unreduced in the suspension together with large platinum-rich particles.…”
Section: Resultssupporting
confidence: 57%
“…For the case that a stabilizer molecule has hydroxyl groups, it also functions as a reductant (for scavenging OH radicals formed by water radiolysis). For instance, glycolate, generated during an electron beam irradiation on a precursor suspension containing EG, functioned as a stabilizer and a reductant at the same time during the radiolytic method (Kugai et al 2015). However, the influence of molecular structure of stabilizers on nanoparticle formation process is complicated and, to our knowledge, only few papers focus on the molecular structure of stabilizers as a factor to control the nanoparticle structure.…”
Section: Introductionmentioning
confidence: 99%
“…42 in the Pt catalyst reducing, resulting in the decrease of oxidation current for Pt-Cu/GNs-CD catalysts. 44,45 It is reported that the excessive amount of non-noble metal may bring about less Pt-rich surface and not be in favor of catalyzing methanol oxidation reaction because that the electro-oxidation of methanol involves multistep adsorption and electron transfer and requires various adjacent Pt active sites. 45 For the same reason, it is found that current density of Pt 1 -Ni 0.7 /GNs-CD (curve b) and Pt 1 -Co 0.4 /GNs-CD (curve b) are the highest among other composites with different metal molar ratio in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A chelate agent, tartaric acid, has been added to enhance the alloying potential of Pt and Ru supported on a carbon support during irradiation with an electron beam of 4.8 MeV at room temperature (3 kGy/s) . More recently, the same group proposed the use of ethylene glycol as an organic stabilizer to promote Pt–Cu alloy formation using the same electron beam irradiation process . The authors claimed that the ethylene glycol protects the Cu metallic clusters and prevents them from the competing oxidation reaction.…”
Section: Methodsmentioning
confidence: 99%
“…73 More recently, the same group proposed the use of ethylene glycol as an organic stabilizer to promote Pt−Cu alloy formation using the same electron beam irradiation process. 74 The authors claimed that the ethylene glycol protects the Cu metallic clusters and prevents them from the competing oxidation reaction. The effect of carboxylate containing compounds on platinum growth has also been studied.…”
Section: Radiolytic Chemistry Involves the Dissociation Of Molecules ...mentioning
confidence: 99%